Exploring the interplay between emotional attitudes towards diabetes, eating behaviour and glycaemic control in patients with type 2 diabetes mellitus - Olívia Garbin Koller; Tamires Freire de Carvalho Santana Andrade; Antônio Bonfada Collares Machado; Jessica Pinto Polet; Bárbara Pelicioli Riboldi; Cíntia Corte Real Rodrigues; Jussara Carnevale de Almeida (Cambridge University Press, 2024)
Abstract Objective: This study aimed to assess the association between emotional attitudes towards diabetes, eating behaviour styles and glycaemic control in outpatients with type 2 diabetes. Design: Observational study. Setting: Endocrinology Division of Hospital de Clínicas de Porto Alegre, Brazil. Participants: Ninety-one outpatients diagnosed with type 2 diabetes. Baseline assessments included data on clinical parameters, lifestyle factors, laboratory results, eating behaviour styles and emotional attitudes. All patients received nutritional counseling following diabetes recommendations. A follow-up visit was scheduled approximately 90 days later to evaluate changes in weight, medication dosages and glycated Hb (HbA1c) values. Patients were categorised based on their emotional attitude scores towards diabetes (positive or negative), and their characteristics were compared using appropriate statistical tests. Results: At baseline, no differences were observed in the proportion of patients with good glycaemic control, eating behaviour styles and emotional attitudes. However, patients with a positive attitude towards the disease exhibited a significantly better response in glycaemic control compared with the reference group (OR = 3·47; 95 % CI = 1·12, 10·75), after adjusting for diabetes duration, sex and medication effect score. However, when BMI was included in the model, the association did not reach statistical significance. Therefore, these results should be interpreted with caution. Conclusions: Patients with a positive attitude towards diabetes showed a greater reduction in HbA1c levels following nutritional counseling. However, baseline BMI could be a potential confounding factor.